2021
DOI: 10.22331/q-2021-08-19-528
|View full text |Cite
|
Sign up to set email alerts
|

Many-Body Quantum Zeno Effect and Measurement-Induced Subradiance Transition

Abstract: It is well known that by repeatedly measuring a quantum system it is possible to completely freeze its dynamics into a well defined state, a signature of the quantum Zeno effect. Here we show that for a many-body system evolving under competing unitary evolution and variable-strength measurements the onset of the Zeno effect takes the form of a sharp phase transition. Using the Quantum Ising chain with continuous monitoring of the transverse magnetization as paradigmatic example we show that for weak measureme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(30 citation statements)
references
References 51 publications
(64 reference statements)
1
29
0
Order By: Relevance
“…Under the skin effect, the system soon reaches a nonequilibrium steady state in which an extensive number of particles are localized at an edge. It is noteworthy that the frozen correlation propagation due to the skin effect is different from the supersonic correlation propagation in non-Hermitian quantum systems with reciprocal dissipation [65,66,68]. This difference also shows a unique role of the skin effect in open quantum systems.…”
Section: A Skin Effectmentioning
confidence: 89%
See 2 more Smart Citations
“…Under the skin effect, the system soon reaches a nonequilibrium steady state in which an extensive number of particles are localized at an edge. It is noteworthy that the frozen correlation propagation due to the skin effect is different from the supersonic correlation propagation in non-Hermitian quantum systems with reciprocal dissipation [65,66,68]. This difference also shows a unique role of the skin effect in open quantum systems.…”
Section: A Skin Effectmentioning
confidence: 89%
“…Non-Hermitian systems have been realized in several open quantum systems, including atoms [52][53][54], photons [55][56][57][58], exciton-polaritons [59], electronic spins [60,61], and superconducting qubits [62]. On the theoretical side, researchers have studied open quantum dynamics of non-Hermitian systems [63][64][65][66][67][68][69][70][71]. Notably, non-Hermitian systems at critical points support anomalous singularities called exceptional points [72][73][74], at which the non-Hermitian Hamiltonians are no longer diagonalizable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, if two states > are perfectly distinguishable, i.e., orthogonal, then we have perfectly indistinguishable; hence, we can measure [ 20 ], first of all, the average time taken for one state (say in our case this is one state initially formed of QZE or collective actualization) to transform into another in general non-orthogonal state before decoherence takes over. This can be shown as the time average of .…”
Section: Discussionmentioning
confidence: 99%
“… Hence, we preserve the overall competition between unitary many body dynamics and the stochastic measurements of single members of an entangled subset of the CAS. Authors have observed [ 20 , 21 ] that such processes involve degrees of freedom that do not commute with each other, for example different components of spin (directions). Starting with a simple one dimensional Ising model, such many body QZE can produce a frozen/localized many body state when the coupling is above critical threshold strength.…”
Section: Methodsmentioning
confidence: 99%